A comparative study of urban crime between Malaysia and Nigeria - Zubairu Abubakar Ghani (Journal of Urban Management, 2017)
Urbanization has created numerous social problems, among which is crime that became a common phenomenon to all urban areas in both developed and developing nations. Recent unimaginable levels of the world urbanization coincides with rise in urban crimes in many parts of the world, as the rate of unemployment had been on the increase and coupled with increased poverty among the urban poor. Nature of crime is not uniform but varies from one geographical region to another. In some areas, property crime is more common while in others, crime on person (violent) is prevalent. Crime is not being plagued by a singular factor anywhere it occurred, there are variant factors that influence criminal activities. However, key factors that persuade criminal behaviours of potential offenders includes: unemployment, poverty, bad governance and weaknesses in law enforcement or crime-control agencies. These four key factors were discussed in this paper with hope of bringing out nature of urban crimes that bedevilled properties and people safety for taking management and prevention measures.